Tourist Loyalty Model through Customer Engagement and Satisfaction: Evaluating the Antecedent Motivational and Recreational Driver - Yosephine Angelina Yulia; Yenni Khristiana; Tri Widianto; Andri Octaviani (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines how motivational drivers (emotional experience and recreational experience) and relational drivers (social presence and self-connection) shape customer engagement and satisfaction, and how these constructs, in turn, drive destination loyalty in the Indonesian tourism context. It further investigates the moderating role of destination type—operationalized through a comparison of mountain-climbing and heritage temple for tourist destinations—in the relationships among these constructs. Design/methodology/approach – An integrated conceptual model incorporating motivational drivers, relational drivers, customer engagement, satisfaction, destination loyalty, and a destination-type moderator was developed and empirically tested. Data were collected via a structured survey of 252 recent tourists visiting Mount Lawu, Mount Merbabu, Prambanan Temple, and Borobudur Temple in July 2025. PLS-SEM (SmartPLS 3.0) and multi-group analysis (MGA) were employed for data analysis. Finding/Results – Eight of ten direct hypotheses are supported. Emotional experience (β = 0.224, p < .01) and recreational experience (β = 0.432, p < .001) significantly influence customer engagement; both also directly affect satisfaction (β = 0.232 and 0.243, respectively). Social presence and self-connection positively influence customer engagement but do not significantly affect satisfaction directly. Customer engagement (β = 0.535, p < .001) and satisfaction (β = 0.328, p < .001) both significantly drive destination loyalty. Satisfaction partially mediates the customer engagement–destination loyalty relationship (indirect effect β = 0.163, p = .002). Multi-group analysis reveals significant between-group differences in three paths: emotional experience → customer engagement, self-connection → customer engagement, and social presence → satisfaction. Originality/Value – This study contributes an integrated nomological network that simultaneously tests the motivational and relational antecedents of customer engagement and satisfaction within a moderated-mediation framework. The study provides empirical evidence that tourist loyalty mechanisms operate across both adventure and heritage destination contexts. The finding that satisfaction partially (rather than fully) mediates the engagement–loyalty link refines mediation theory in tourism.